Application of international classification of functioning, disability and health in salat: a scoping review - Irma Ruslina Defi; Intan Sabrina Mohamad; Nuzula Chafidh Al Barqi; Adziqa Ammara Qiantori; Andri Qiantori (Faculty of Medicine, Universitas Trisakti, 2025)
BackgroundSalat has been linked to physical, cognitive, emotional and psychological health benefits. This scoping review classifies the health benefits of salat based on the International Classification of Functioning, Disability, and Health (ICF) conceptual framework. The ICF illustrates how Salat may be used as a multi-modal and multidisciplinary framework to rehabilitate clients with different conditions tailored to their clinical, psychosocial and environmental contexts.PurposeTo conduct a scoping review on the health benefits of salat (muslim prayer) based on the ICF conceptual framework.MethodsA literature review was conducted from February to April 2023 using PubMed, EBSCO, and the Scopus Library databases. Articles published between 2012 and 2023 were retrieved using the following keywords: